STRATEGI MENINGKATKAN DAYA SAING UMKM WARUNG MAKAN BU HAFID DI ERA DIGITAL - Achmad Wicaksono; Devi Maya Sofa (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2026)
The aim of this research is to formulate a strategy to increase the competitiveness of the Warung Bu Hafid MSME. The research was conducted using a qualitative descriptive method. Research data were obtained through in-depth interview techniques, direct observation, and documentation study. The collected data were analyzed through the SWOT framework to identify internal and external factors affecting business competitiveness. The research results identified strengths including strategic location, affordable prices, and delicious food quality, while weaknesses encompass minimal online promotion, lack of digital technology utilization, and monthly sales fluctuations. Opportunities that can be leveraged are local community consumption needs, community empowerment, takeaway services, and busy lifestyle trends, whereas threats include changes in consumer habits, rising raw material prices, dependence on local markets, and digital competition. Based on the SWOT matrix, the research formulated four strategy categories: SO Strategy (developing practical meal packages and pre-order services), WO Strategy (forming local digital teams and late-month promotions), ST Strategy (loyal customer ambassador programs and